Systemy algebry komputerowej a nauczanie matematyki i przedmiotów pokrewnych - Zawadzki, Henryk (Computer Algebra Systems in Teaching Mathematics and Related Subjects, 2006)
Computer Algebra Systems (CAS) are type of software package that is used in manipulation of mathematical formulae. The main purpose of this article is to provide arguments justifying thesis that the role of CAS as a tool supporting didactic process should increase. In author's opinion the ability to use CAS should become as common among students, as ability to use word processors, spreadsheets and Internet. The article contains information about some well known CAS and their capabilities. It also describes benefits students and lecturers can achieve using this kind of software. The article ends up with some remarks on accessibility of CAS and perspectives of their use in teaching mathematics and related subjects at polish universities.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1117, s. 194-197